External Economies and International Trade Redux: Comment* - Lyn, Gary; Rodríguez-Clare, Andrés (Quarterly Journal of Economics, 2013)
Abstract Recently, Gene Grossman and Esteban Rossi-Hansberg (GRH; “External Economies and International Trade: Redux,” Quarterly Journal of Economics 125 [2010], 829–858) proposed a novel way to think about the implications of international trade in the presence of national external economies at the industry level. Instead of perfect competition and two industries, GRH assume Bertrand competition and a continuum of industries. GRH conclude that the equilibrium is unique if transport costs are low, that there is no trade for high transport costs, and that there is no equilibrium in pure strategies when transport costs are intermediate. In this note we reexamine the equilibrium analysis under different transport costs for a single industry (partial equilibrium) version of GRH’s model. We confirm many of GRH’s results, but also find that there are circumstances under which there are multiple equilibria, including equilibria in which trade patterns run counter to “natural” comparative advantage, and also find that there is a profitable deviation to the mixed-strategy equilibrium postulated by GRH for intermediate trading costs. We propose an alternative set of strategies for this case and establish that they constitute an equilibrium.